Volatility characteristics of stocks underlying Exchange Traded Funds in South Africa - Matarutse, Justice (Journal of Economics and Behavioral Studies, 2014)
Exchange Traded Funds (ETFs), since their inception, are now taking a foothold in emerging markets. The study measures price volatility in ETFs and their underlying stocks before and after ETF inception so as to provide new evidence of the volatility implications of ETFs for financial markets. The analysis focuses on the Johannesburg Stock Exchange (JSE) SatrixTop40 ETF and its components using an EGARCH (1, 1) model. The analysis focuses on leverage effects, absolute size of volatility innovations and volatility persistence, and concludes that these volatility characteristics have changed and/or increased after the Satrix Top40 ETF introduction on the JSE.